Hubungan BBLR dengan Stunting pada Anak Usia 2-5 Tahun di Desa Sidan Gianyar Tahun 2019 - Putu Kania Ayu Kirana; Ni Putu Aniek Mahayani; Anak Agung Gede Indraningrat (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Stunting is a condition that fails to grow in children under five so that the child becomes too short for his age. The standard stunting measurement is based on the body length index compared to age (PB / U) or height compared to age (TB / U) with a limit (z-score) less than -2 SD from the WHO child growth nutritional status table. Stunting events are influenced by several factors, one of which is Low Birth Weight (LBW). The purpose of this study was to find out if there is a LBW relationship with stunting events in children aged 2-5 years in Sidan Village of Health Center Gianyar I Working Area in 2019. This study is a analitic study with a case control approach. The sample in this study was all children aged 2-5 years in sidan village. This research sampling technique is a total sampling with a sample number of 58 respondents who meet the criteria of inclusion and exclusion. Data collection using observation sheets and mother and child health (KIA) books. Data analysis using the Chi-square test with Î±=0.05. In this study obtained the results: the frequency of stunting the most in the age range of 24-36 months as many as 12 children. Of the 58 children, there were 26 children with a history of LBW, including in the stunting group as many as 21 children and in the group of not stunting as many as 5 children. From this study, it was concluded that there is a historical relationship between LBW and stunting events in children aged 2-5 years in Sidan Village of Health Center Gianyar I Working Area in 2019 (p: 0.000; OR: 12,000; 95% CI: 3,569-44,488).